Обліково-інформаційний аспект оцінювання фінансово-економічної ефективності екологічного менеджменту аграрних підприємств - Рібейро Рамос, О.О. (Управління економікою: теорія та практика, 2020)
Узагальнено обліково-інформаційний аспект оцінювання фінансово-еконо¬мічної ефективності екологічного менеджменту аграрних підприємств. Визначено тенденцію до зниження використання пестицидів в агропромисловому виробництві, що вказує на прагнення товаровиробників до вироблення органічної продукції з мінімальною кількістю хімічних речовин. Проаналізовано загальнодержавний тренд з упровадження безвідходного або маловідходного виробництва. Сформовано комплекс показників оцінювання ефективності системи екологічного менеджменту аграрних підприємств на основі показників впливу на природне оточення та біоту, показників залучення виробничого потенціалу підприємства до екологізації та природозбереження, показників фінансових витрат на природозбереження. Розроблено шкалу ранжування комплексного показника та встановлено його залежність від системи запропонованих показників. Визначено перспективу подальших досліджень щодо апробації оцінювання ефективності системи екологічного менеджменту за запропонованими показниками на прикладі аграрних підприємств України. Обобщён учетно-информационный аспект оценки финансово-экономичес¬кой эффективности экологического менеджмента аграрных предприятий. Определена тенденция к снижению использования пестицидов в агропромышленном производстве, что указывает на стремление товаропроизводителей к производству органической продукции с минимальным количеством химических веществ. Проанализирован общегосударственный тренд по внедрению безотходного или малоотходного производства. Сформирован комплекс показателей оценки эффективности системы экологического менеджмента аграрных предприятий на основе показателей воздействия на окружающую среду и биоту, показателей привлечения производственного потенциала предприятия в экологизацию и охрану природы и показателей финансовых затрат на охрану природы. Разработана шкала ранжирования комплексного показателя и установлена его зависимость от системы предложенных показателей. Определены перспективы дальнейших исследований по апробации оценки эффективности системы экологического менеджмента по предложенным показателям на примере аграрных предприятий Украины. The article summarizes the accounting and informational evaluation of the financial and economic efficiency of agricultural enterprises environmental management. There is a tendency to reduce the use of pesticides in agro-industrial production, which indicates the desire of producers to produce organic products with a minimum amount of chemicals. The national trend of introduction of waste-free or low-waste production is analyzed. A set of indicators for assessing the effectiveness of the environmental management system of agricultural enterprises based on indicators of impact on the environment and biota (allows to determine the depth of environmental impact from the activities of agricultural enterprises), indicators of attracting production potential of the enterprise for greening between the consumed and reproduced resource of the enterprise) and nature conservation and indicators of financial costs for nature conservation (determine the amount of costs incurred by the agricultural enterprise for the preservation of the environment and biota). To assess the effectiveness of the environmental management system of agricultural enterprises, it is proposed to determine its comprehensive indicator according to these three components. The ranking scale of the complex indicator is developed and its dependence on the coefficient of emissions of hazardous substances into the air by the agricultural enterprise is determined; the coefficient of wastewater emissions into the environment by an agricultural enterprise; the coefficient of waste-free production by an agricultural enterprise; the coefficient of impact on the environment due to accidents at the enterprise; the coefficient of costs for the protection of the natural environment and biota; coefficient of investments involved in the protection of the natural environment and biota; current liquidity ratio; the coefficient of renewal of obsolete fixed assets for environmentally friendly; depreciation ratio; depreciation ratio of fixed assets; coefficient of environmental friendliness of production processes. A ranking scale for each of the components of the integrated indicator is proposed. The prospect of further research is determined, which is based on the need to test the evaluation of the effectiveness of the environmental management system on the proposed indicators on the example of agricultural enterprises of Ukraine.